2008
DOI: 10.1007/s00417-007-0744-9
|View full text |Cite
|
Sign up to set email alerts
|

Tissue bioengineering for surgical bleb defects: an animal study

Abstract: OloGen successfully serves as a 3-dimensional scaffold for cell migration and proliferation, and can prevent failure by maintaining the size of the bleb in the presence of a large wound defect. It might also be successful at repairing postoperative bleb leaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 20 publications
1
78
0
5
Order By: Relevance
“…It led to a randomised collagen deposition and microcyst formation after penetrating anti-glaucomatous surgery in contrast to the negative control and decreased early postoperative scarring. 8,9 Moreover, the ologen implant will also be adjuvant in repairing postoperative bleb leaks. 9 In human subjects, the ologen implant was tested for augmentation in deep sclerectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It led to a randomised collagen deposition and microcyst formation after penetrating anti-glaucomatous surgery in contrast to the negative control and decreased early postoperative scarring. 8,9 Moreover, the ologen implant will also be adjuvant in repairing postoperative bleb leaks. 9 In human subjects, the ologen implant was tested for augmentation in deep sclerectomy.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Moreover, the ologen implant will also be adjuvant in repairing postoperative bleb leaks. 9 In human subjects, the ologen implant was tested for augmentation in deep sclerectomy. This study revealed that deep sclerectomy with ologen implantation is an effective and well-tolerated method for reduction of IOP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also helps to separate the conjunctiva and episcleral surface preventing adhesions between them. 6 Most of the studies have compared between ologen and mitomycin C (MMC) in primary glaucoma or in primary and secondary glaucomas collectively. Also, studies stated that there was no difference in the success rate between trabeculectomy in cases of open angle and angle closure glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…9,14,15 Recently, a new biodegradable porous collagen-glycosaminoglycan (GAG) copolymer matrix implant has been proposed for glaucoma surgery on the basis of animal experiments. [16][17][18] Ologen (OLO) collagen matrix (Aeon Astron Europe BV, Leiden, The Netherlands) is a biodegradable collagen-GAG implant, available in various shapes and dimensions, that may maintain the hypotensive effect in glaucoma surgery and enhance the healing in other selected ophthalmic surgeries (eg, pterygium or strabismus). According to the manufacturer, when the OLO is directly placed over the scleral flap, its porous structure should force conjunctival fibroblasts and myofibroblasts to grow into the pores and secrete connective tissue in the form of a loose matrix, reducing scar formation and wound contraction.…”
Section: Introductionmentioning
confidence: 99%